2011
DOI: 10.1080/02646838.2011.593030
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, wellbeing and parenting in mothers of infants and toddlers with sleep problems

Abstract: Objective: This study explored the relationships between fatigue, wellbeing and parenting in mothers of young children (aged 0-4 years) with sleep and settling difficulties. Demographic, child sleep and maternal factors associated with fatigue were also investigated. Background: Children's sleep problems can have a significant impact on parent's sleep, placing them at risk of fatigue and wellbeing difficulties. Methods: A total of 164 mothers of children aged 0-4 attending an early parenting centre completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 29 publications
(33 reference statements)
7
80
1
1
Order By: Relevance
“…However, the definition of sleep problems differs between research groups. Studies have shown that mothers of young children with (persistent) sleep difficulties experience poorer physical and mental health [5,6], tend to be more depressed [7][8][9][10][11] and anxious [12], and report higher stress [4,[12][13][14]. The direction concerning some of these associations -especially relating to maternal depression -is supported by two kinds of results.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, the definition of sleep problems differs between research groups. Studies have shown that mothers of young children with (persistent) sleep difficulties experience poorer physical and mental health [5,6], tend to be more depressed [7][8][9][10][11] and anxious [12], and report higher stress [4,[12][13][14]. The direction concerning some of these associations -especially relating to maternal depression -is supported by two kinds of results.…”
Section: Introductionsupporting
confidence: 67%
“…Following recommendations by Brockington [62], further studies should distinguish between harm-related obsessive thoughts in mothers who are gentle and devoted and pathological anger that precedes child abuse. As mentioned by Giallo et al [12], a high level of aggression (and depression or anxiety) may contribute to the mental and physical experience of fatigue. The authors explored mothers of young children (0-4 years of age) with sleep and settling difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parents performed considerable demanding care work to help their children get to sleep, while they themselves often experienced reduced or disturbed sleep, leaving them tired and exhausted. This was also highlighted in other studies (Cooklin, Giallo, & Rose, 2012; Giallo, Rose, Cooklin, & McCormack, 2013; Giallo, Rose, & Vittorino, 2011), and is something that can be seen in the context of the experience of fatigue among parents, including after the first few years of a child’s life (Cooklin et al, 2012). It is known that sleep problems in small children can be emotionally difficult for mothers (Hiscock et al, 2008).…”
Section: Discussionsupporting
confidence: 53%
“…They articulated a narrative of infant sleep in which frequent waking is normal The literature on postpartum depression suggests that management of parental expectations prior to birth may prevent frustration and unfulfilled expectations of parental ability and self-efficacy (Ball, 2003;Kennedy et al, 2007). Unrealistic expectations of infant and parental sleep are associated both with higher levels of self-reported fatigue (Giallo, Rose, & Vittorino, 2011) and with negative cognition linked to depression (Muscat, Thorpe, & Obst, 2012). The emergence of a new narrative around infant sleep in the context of an increased premium on exclusive breastfeeding may reflect the efforts of breastfeeding mothers to consolidate the validity of their own experiences and re-align the expectations of prospective new parents with a "new reality" of night-time infant care.…”
mentioning
confidence: 99%